Kan Eslöv kan alla? En studie av Eslövs kommuns skolbibliotekssatsning - Höglund,Mari; Dietrichson,Maria (2025)
In 2024 Eslöv published an initiative to invest in the municipalities’ school libraries. Focusing on equality, the desired effect of the school library initiative was described as increased student results and reading. In light of the coming changes in The Education Act, we argue that the initiative is interesting to study. The purpose of this essay is to contribute with knowledge about what characterizes a long term and sustainable school library program. We will describe the initiative in Eslöv and, drawing on previous research, we will identify characteristics of a sustainable school library program and discuss if the initiative in Eslöv contains these characteristics. The study is framed by theories of infrastructure and boundary infrastructures. Using interviews and surveys, we have examined Eslöv’s initiative and analysed the responses using reflexive thematic analysis and our theoretical framework. Through our analysis we have identified that there is a predominantly positive attitude towards the initiative among our informants. Equality, cooperation and organization emerge as central themes in our analysis. Our conclusion is that boundary infrastructures within school and municipality are crucial for sustainable school library development. Furthermore, we find that decisions regarding school library programs need to be made at the municipal level to achieve equality. The role of the headmaster is important in achieving long term and sustainable school library development; here our findings correlate with previous research. Likewise, it is of great importance that a coordinated evaluation takes place. Such an evaluation should go beyond an analysis of the workings of the school library and consider the effects of the school library program, thereby ensuring the possibility to identify the effect of school library initiatives like the one in Eslöv.
Keywords: Library; Information; School libraries; School librarians; Taxonomies; Infrastructure theory; Boundary infrastructures